2005
DOI: 10.1196/annals.1334.008
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Blood‐Derived Stem Cells and Brain Repair

Abstract: Human umbilical cord blood (HUCB) is now considered a valuable source for stem cell-based therapies. HUCB cells are enriched for stem cells that have the potential to initiate and maintain tissue repair. This potential is especially attractive in neural diseases for which no current cure is available. Furthermore, HUCB cells are easily available and less immunogenic compared to other sources for stem cell therapy such as bone marrow. Accordingly, the number of cord blood transplants has doubled in the last yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 70 publications
1
82
0
2
Order By: Relevance
“…It has been reported that HUCBC entry into the brain is not required to promote neuroprotection [59]. According to the report just outlined, recovery following brain injury is mediated through peripheral anti-inflammatory responses resulting in brain recovery [9]. This is in accord with our results that indicated more of a peripheral, HUCBCmediated CNS affect, since the cells were not detected in the mouse brain for any significant amount of time.…”
Section: Figsupporting
confidence: 82%
See 3 more Smart Citations
“…It has been reported that HUCBC entry into the brain is not required to promote neuroprotection [59]. According to the report just outlined, recovery following brain injury is mediated through peripheral anti-inflammatory responses resulting in brain recovery [9]. This is in accord with our results that indicated more of a peripheral, HUCBCmediated CNS affect, since the cells were not detected in the mouse brain for any significant amount of time.…”
Section: Figsupporting
confidence: 82%
“…We conducted an analysis of mouse brain homogenates using monoclonal Ab [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] antibody (6E10) to analyze Ab species and b-C-terminal fragments (b-CTFs), from both the 6-and 10-month treated groups. The 6E10 antibody specifically recognizes APP and b-CTFs.…”
Section: Cerebral Parenchymal B-amyloid Plaques Are Reduced In Ad Tramentioning
confidence: 99%
See 2 more Smart Citations
“…A few promising experimental studies using human UCB (hUCB)-derived mononuclear cells and hUC-derived mesenchymal stem cells (hUC-MSCs), either from the blood or from Wharton's jelly, have already been undertaken (5)(6)(7)(8). Thus, there is increasing interest in studying the potential of UC-derived stem cells for the treatment of brain diseases (9). This review will summarize the most recent data on the technical aspects and the preclinical use of hUC-MSCs, which are opening up promising perspectives in the neuroprotection and neuroregeneration of the developing human brain.…”
mentioning
confidence: 99%